Agrobacterium tumefaciens responses to plant-derived signaling molecules - Subramoni, Sujatha; Nathoo, Naeem; Klimov, Eugene; Yuan, Ze-Chun (Frontiers in Plant Science, 2014)
As a special phytopathogen, Agrobacterium tumefaciens infects a wide range of plant hosts and causes plant tumors also known as crown galls. The complexity of Agrobacterium–plant interaction has been studied for several decades. Agrobacterium pathogenicity is largely attributed to its evolved capabilities of precise recognition and response to plant-derived chemical signals. Agrobacterium perceives plant-derived signals to activate its virulence genes, which are responsible for transferring and integrating its Transferred DNA (T-DNA) from its Tumor-inducing (Ti) plasmid into the plant nucleus. The expression of T-DNA in plant hosts leads to the production of a large amount of indole-3-acetic acid (IAA), cytokinin (CK), and opines. IAA and CK stimulate plant growth, resulting in tumor formation. Agrobacterium utilizes opines as nutrient sources as well as signals in order to activate its quorum sensing (QS) to further promote virulence and opine metabolism. Intriguingly, Agrobacterium also recognizes plant-derived signals including γ-amino butyric acid and salicylic acid (SA) to activate quorum quenching that reduces the level of QS signals, thereby avoiding the elicitation of plant defense and preserving energy. In addition, Agrobacterium hijacks plant-derived signals including SA, IAA, and ethylene to down-regulate its virulence genes located on the Ti plasmid. Moreover, certain metabolites from corn (Zea mays) also inhibit the expression of Agrobacterium virulence genes. Here we outline the responses of Agrobacterium to major plant-derived signals that impact Agrobacterium–plant interactions.